ANALISIS SISTEM DINAMIK USAHATANI TANAM SAYURAN BERKELANJUTAN BERBASIS PENGENDALIAN HAMA TERPADU DI KABUPATEN TANGGAMUS, PROVINSI LAMPUNG - Sudiono Sudiono; S. H. Sutjahyo; P. Hidayat; R. Kurniawan (Universitas Lambung Mangkurat, 2019)
The purpose of this study was to develop a dynamic model of sustainable farming based on an integrated pest management system in upland vegetable crops in Tanggamus Regency, Lampung Province. Dynamic system analysis with powersim with the stages of model development, namely needs analysis, problem formulation, system identification, model simulation, and model testing. The results of the compilation of the dynamic model parameters, namely the current scenario (without intervention), in 2017 farmer households amounted to 104,929 households which increased in 2030 to 128,613 households farmers' income at the end of the simulation period to Rp 434,526,807 from a land area of 4,029 ha, scenario pessimistic in 2017 farmer households amounted to 100,753 households which experienced an increase in 2030 to 116,252 households with income in this scenario to Rp 470,170,405 from a land area of 4,243 ha, and an optimistic scenario for 2017 farmers' households amounting to 100,111 households that had increased in the year 2030 became 107,892 households with total farmer's income of Rp 508,916,172 on an area of 4,464 ha.